2008
DOI: 10.1021/ja804516q
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal Lead Sulfide Crystallites With High Energy {113} Facets

Abstract: A new, generic method to exercise control over the shape of crystallites is reported. Crystals of PbS are grown in the unusual form of pyramids at the water-toluene interface. The pyramids are single crystalline and adopt a unique growth habit (slow growth along [113] direction). The pyramids are exclusive products of the reaction and are obtained in the form of a monolayered film spread across the fluid interface. The origins of the growth habit and assembly lie in phenomena unique to the liquid-liquid interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 21 publications
0
51
0
Order By: Relevance
“…Particularly, high-energy facets that contain abundant unsaturated coordination atoms and atomic steps and ledges usually exhibit high reactivity. [1][2][3][4][5][6][7] However, during the crystal growth process, the high-energy facets quickly disappear to minimize the surface energy of the crystals. Control of the exposed high-energy crystal facets is still a challenging research topic, especially for metal oxides, in which the surface energy is very difficult to modify because of the strong metal-oxygen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, high-energy facets that contain abundant unsaturated coordination atoms and atomic steps and ledges usually exhibit high reactivity. [1][2][3][4][5][6][7] However, during the crystal growth process, the high-energy facets quickly disappear to minimize the surface energy of the crystals. Control of the exposed high-energy crystal facets is still a challenging research topic, especially for metal oxides, in which the surface energy is very difficult to modify because of the strong metal-oxygen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Much success has been achieved in the investigation of the structural effects of nanocrystals on catalysis and the results showed that the catalytic performance could be specifically regulated either by the crystal size or morphology with distinct crystallographic planes. [17][18][19][20][21] The reason might be that different crystal sizes or planes exhibit different numbers of dangling bonds and different atom arrangement manners, which intrinsically determine the reactivity and selectivity of catalysts. For instance, Co 3 O 4 nanosheets with exposed {112} planes exhibited enhanced catalytic activity for methane combustion than Co 3 O 4 nanobelts with {011} planes and nanocubes with {001} planes.…”
Section: Introductionmentioning
confidence: 99%
“…For example, PbS nanocrystals have been shown to change from sphere to rod growth by simply altering the structure of the Pb source. 8 Herein, we have identied a class of complexes based on the thiobiuret ligand all of which are found suited for deposition of binary metal suldes at the water-toluene interface.…”
Section: -7mentioning
confidence: 99%
“…Molecular precursor mediated interfacial deposition of nanostructures is one such scheme. A recent revival of interest in this area [5][6][7] has led to materials of topical interest such as thin lms made of pyramidal PbS nanocrystals bound by high energy {331} surfaces, 8 nanorod structures of CdS 9 and Bi 2 S 3 .…”
Section: Introductionmentioning
confidence: 99%